The Manager inside the minds of football's leaders - Carson, Mike (Michigan Brilliance Audio, 2013)
From the post room to the board room, everyone thinks they can be the manager. But how do you manage outrageous talent? What do you do to inspire loyalty from your players? How do you turn around a team in crisis? What?s the best way to build long-term success? How can you lead calmly under pressure?
Keywords: Management